Biologia reprodutiva de Helicops infrataeniatus (Serpentes: Dipsadidae) da região subtropical do Brasil - Moura, Livia Bataioli (2017)
ABSTRACT 1: Reproductive biology studies are funtamental for the understanding of of the life history of a species. In this work we describe the reproductive biology of the males of Helicops infrataeniatus in a Brazilian subtropical climate environment. For this morpho-anatomical and histological analysis were realized of individuals deposited in zoological collections. The reproductive cycle was described through seasonal variation in the reproductive organs: testes, kidneys and ductus deferents. Spermatogenesis occurred during late autumn–winter (June–September), spermiogenesis occurred in spring (September–December) and complete regression of the testis were in autumn (April-May). The testis showed hypertrophy in summer (January-March), while ductus deferents presented spermatozoa all over the year and did not show seasonal variation due to sperm storage. The kidney showed increase in spring (October-December), however the tubular diameter of the sexual segment of the kidney (SSK) was increase in winter (July-Setember). Therefore, at the individual level, males exhibit a discontinuous cyclical reproduction, while population level, the reproductive cycle is seasonal semisynchronous. Finally, we discuss intrinsic and extrinsic factors that influence the reproductive strategies of H. infrataeniatus.